Imprensa, ditadura e democracia - Pires, Elaine Muniz (2008)
The present dissertation aims to contribute for the understanding of the current Brazilian press history through the study of the process of the emergency of the newspaper Folha de S.Paulo as one of the most important newspapers of the Brazilian mass media. Our research studies the consolidation of Grupo Folha and its relations with military governments and with the historical juncture of the fight against the dictatorship, focusing the debate about the construction of the image of a democratic and independent newspaper. This study begins in the 80s, when Grupo Folha decided to invest in the construction of a image which could brought prestige to the newspaper and to achieve commercial success for the enterprise. The first chapter explores the performance of Folha de S.Paulo in the process of the construction of its image as a defender of democratic values, mainly from its engagement on the campaign for direct presidential elections, the Diretas-Já campaign. The second chapter approaches the continuity of this trajectory in the 80s and 90s, emphasizing the marketing strategies and the publications that remember the engagement of Folha de S.Paulo in the transition from dictatorship to democracy, concomitantly to the reformulation of the newspaper implemented from its editorial project and manual of style. Finally, we analysed controversies over the relations of the Grupo Folha with the civil-military regime revealed by academic works since 1999